Revitalisasi Literasi Global: Pengembangan Kampung Inggris Sapen sebagai Pusat Pembelajaran Bahasa Inggris Inovatif di Yogyakarta - Endarwati, Maria Lies; Mustikasari, Anita; Nababan, Donald Jupply; Utama, Agung; Sony, Arya (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The Sapen English Village in Yogyakarta faces challenges in improving English literacy, particularly among children, due to the limited availability of appropriate teaching materials and the lack of interactive learning methods. To address these issues, this community service program adopts a sustainable training approach, develops the English for Children learning module, and utilizes open-source materials to enhance the quality of learning. The activities include training local tutors, implementing the module in the teaching and learning process, and evaluating learning outcomes through pre-tests and post-tests. The results indicate a significant improvement in the children’s English proficiency, with the average post-test scores increasing by 26% compared to the pre-test scores. These findings demonstrate that the integration of interactive modules and open-source materials provides an effective solution to the limitations of learning resources. Overall, the program has successfully developed a relevant and sustainable model for empowering English literacy, which has the potential to enhance the local community’s competitiveness in the global era.